THE WORLD AND DOMESTIC MARKETS FOR TOBACCO AND TOBACCO PRODUCTS - Đorović, Milutin; Stevanović, Simo; Lazić, Verica (Economics of Agriculture, 2012)
This paper presents a regional comparative analysis of the major indicators of both the world and domestic markets of tobacco and tobacco products. Namely, for the last 21 years, for the observed sub-periods, the method of comparative analysis were used to study quantitative and structural differences in the production and trade of analyzed product groups, at both the world and at the level of continents and some countries. The leading manufacturers and flows of international trade and the leading exporters and importers of tobacco and tobacco products were defined, with special emphasis on the importance of Serbia, i.e. its position in the global market for these products. Pursuant to the above, and importance of analyzed product groups for the domestic market, i.e. agriculture, agro-industry and the economy as a whole, this paper specially studies balances, structure, dynamics and regional orientation of foreign trade exchange in tobacco and tobacco products. In addition, the paper points to the needs, capabilities, measures and directions of further development of domestic production and export of products analyzed.